Eccentric strengthening effect of hip-adductor training with elastic bands in soccer players: a randomised controlled trial - Jensen, J.; Hölmich, P.; Bandholm, T.; Zebis, M. K.; Andersen, L. L.; Thorborg, K. (British Journal of Sports Medicine, 2014)
Background: Soccer players with weak hip-adductor muscles are at increased risk of sustaining groin injuries. Therefore, a simple hip-adductor strengthening programme for prevention of groin injuries is needed.Objective We aimed to investigate the effect of an 8-week hip-adductor strengthening programme, including one hip-adduction exercise, on eccentric and isometric hip-adduction strength, using elastic bands as external load. Methods: Thirty-four healthy, sub-elite soccer players, mean (±SD) age of 22.1 (±3.3) years, were randomised to either training or control. During the mid-season break, the training group performed 8 weeks of supervised, progressive hip-adduction strength training using elastic bands. The participants performed two training sessions per week (weeks 1-2) with 3×15 repetition maximum loading (RM), three training sessions per week (weeks 3-6) with 3×10 RM and three training sessions per week (weeks 7-8) with 3×8 RM. Eccentric hip-adduction (EHAD), isometric hip-adduction (IHAD) and isometric hip-abduction (IHAB) strength, and the IHAD/IHAB ratio were measured assessor-blinded preintervention and postintervention, using reliable hand-held dynamometry procedures. Results: In the training group, EHAD strength increased by 30% (p<0.001). In the control group, EHAD strength increased by 17% (p<0.001), but the increase was significantly larger in the training group compared with the control group (p=0.044). No other significant between-group strength-differences in IHAD, IHAB or the IHAD/IHAB ratio existed (p>0.05). Conclusions: 8 weeks of hip-adduction strength training, using elastic bands, induce a relevant increase in eccentric hip-adduction strength in soccer players, and thus may have implications as a promising approach towards prevention of groin injuries in soccer.